Effects of ascorbic acid on Chlamydia trachomatis infection and on erythromycin treatment in primary cultures of human amniotic cells. - Wang, S K (1992)
Ascorbic acid (vitamin C) is an essential nutrient for humans. It may also be needed by Chlamydia trachomatis, an intracellular bacterium. We investigated the effects of vitamin C on the growth of C. trachomatis E/UW-5/Cx in a primary culture of human amniotic epithelial cells. The results showed that vitamin C enhances C. trachomatis infection at concentrations of 0.2, 0.6, and 1.2 mg/dl (P less than 0.001). These three concentrations represent the in vivo concentrations of deficiency, normal, and overload levels in serum, respectively. The enhancement was dose dependent. However, the growth of C. trachomatis was inhibited at vitamin C concentrations of 120 and 1,200 mg/dl. The inhibitory effect of erythromycin against C. trachomatis was shown to be reduced in the presence of vitamin C at the three concentrations tested (P less than 0.025-0.001), and MICs were four times greater (1.6 versus 0.4 micrograms/ml). Human amniotic cells were tolerant to vitamin C concentrations of up to 1,200 mg/dl. The results show that vitamin C may be an important nutrient for C. trachomatis and that incorporation of vitamin C in the culture medium may enhance the isolation and propagation of C. trachomatis in cell cultures.